Status of Locals in the Development of Citie of Uzbekistan - Sereeva Guljazira Adilbaevna (Research Parks Publishing LLC, 2021)
At the current stage of urban development in Uzbekistan, it is necessary to sharply increase housing construction in the city. This is due to the high rate of natural population growth, low level of housing, large amount of old housing stock in large and large cities, as well as other peculiarities of the republic. This article also discusses these issues and the role of makhalla institutions.